POTENSIAL FISHING GROUND MAPPING OF SKIPJACK AND FRIGATE TUNA IN NORTH NANGGROE ACEH DARUSSALAM WATERS - Muklis Muklis; Jonson Lumban Gaol; Domu Simbolon (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2009)
Potential fishing ground mapping of skipjack and frigate tuna was determined based on sea surface temperature (SST) and chlorophyll-a concentration. The objectives of study were to analyze the temporal and spatial variability of SST and chlorophyll-a and it’s relationship on potential fishing ground. Chlorophyll-a concentration and SST were derived from Moderate Imaging Spectroradiometer (MODIS) sensors using SeaDAS image processing software. Catch data of skipjack and frigate tuna collected from Lampulo fishing base, Banda Aceh from January 2006 until November 2007. Linier regression was used to analysis relationship between catch perunit effort (CPUE) of fish and oceanographic parameters. The analysis of SST and chlorophyll-a concentration showed the temporal and spatial variations in northern part of Aceh seawaters. Both of Chlorophyll-a concentration and SST have positive relationship on CPUE of skipjack and frigate tuna.Keywords: Mapping, potential fishing ground, skipjack and frigate tuna, North Nanggroe Aceh Darussalam Waters, chlorophyll-a, SST.